Fuentes del Derecho y precedentes constitucionales: encuentros y desencuentros en el sistema de justicia del Perú - Díaz Colchado, Juan Carlos (2022)
The paper explores the tensions raised within the Peruvian justice system between different legal sources due to the incorporation of binding constitutional precedent. The Peruvian legal system is ascribed to the family of civil law, where the law is the main source, however, the precedent is an institution of common law systems, where this is the most important source of law, which generates agreements and disagreements. Added to this is the convergence of two processes that are reconfiguring the sources of Peruvian law: the constitutionalization and conventionaliza-tion of law.Therefore, for the Peruvian justice system, the treatment that should be given to the agreement and disagreement that provokes the tensions between the constitutional precedent with the law, with the ordinary precedent and with the inter-American standards, represents a challenge.